Respuesta :
Hello!!
So, the point slope equation is y-y₁=m(x-x₁)
In order to solve this with the points (-3,2) and (2,1), you need to find the slope.
The equation to find the slope is m=(y₂-y₁)/(x₂-x₁):
m=(2-1)/(-3-2)
m= -1/5
So your slope is-1/5
Now, using the point slope equation I stated earlier, ^^^ plug in either of the points you were given (Either -3,2 or 2,1) and your slope or m value (-1/5)
I'll show you both of the possible equations:
1) Using (-3,2)
y-(2)=m(x-(-3)) OR y-(2)=m(x+3)
Add 2 to both sides
y=mx+5
Answer is y=mx+5
2) Using (2,1)
y-(1)=m(x-(2))
Add 1 to both sides
y=mx-1
Answer is y=mx-1
Hope this helps!!!!
So, the point slope equation is y-y₁=m(x-x₁)
In order to solve this with the points (-3,2) and (2,1), you need to find the slope.
The equation to find the slope is m=(y₂-y₁)/(x₂-x₁):
m=(2-1)/(-3-2)
m= -1/5
So your slope is-1/5
Now, using the point slope equation I stated earlier, ^^^ plug in either of the points you were given (Either -3,2 or 2,1) and your slope or m value (-1/5)
I'll show you both of the possible equations:
1) Using (-3,2)
y-(2)=m(x-(-3)) OR y-(2)=m(x+3)
Add 2 to both sides
y=mx+5
Answer is y=mx+5
2) Using (2,1)
y-(1)=m(x-(2))
Add 1 to both sides
y=mx-1
Answer is y=mx-1
Hope this helps!!!!
Answer:
[tex]y=-\frac{x}{5}+\frac{7}{5}[/tex]
Step-by-step explanation:
We need to find the equation of a line that passes through the points [tex]\left ( -3, 2 \right )[/tex] and [tex]\left ( 2, 1 \right )[/tex].
We know that the point slope form of a line passing through [tex]\left ( x_{1}, y_{1} \right )[/tex] and with slope m is [tex]y-y_{1}=m\left ( x_{1}-y_{1} \right )[/tex]
So, first we need to find the slope, m.
We know that [tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}}[/tex]
Here, [tex]x_{1}=-3, x_{2}=2, y_{1}=2,y_{2}=1[/tex]
So, [tex]m=\frac{1-2}{2-(-3)}=-\frac{1}{5}[/tex]
Now, the equation of the line is
[tex]y-2=-\frac{1}{5}\left ( x-\left ( -3 \right ) \right )[/tex]
[tex]\implies y-2=-\frac{1}{5}\left ( x+3 \right )[/tex]
[tex]\implies y-2=-\frac{x}{5}-\frac{3}{5}[/tex]
[tex]\implies y=-\frac{x}{5}-\frac{3}{5}+2[/tex]
[tex]\implies y=-\frac{x}{5}+\frac{7}{5}[/tex]
Hence, the equation is [tex]y=-\frac{x}{5}+\frac{7}{5}[/tex]